Monetary policy and foreign direct investment: Empirical evidence - Nguyen Van Chien (Economies, 2023)
The purpose of this study is to evaluate the impact of monetary policy on attracting foreign direct investment. We used data for typical countries in Southeast Asia for the period 1997 to 2020, using regression of least squares (OLS), fixed effects (FEM) and random effects (REM), as well as cross-sectional dependence test based on panel-corrected standard errors (PCSE) and Driscoll Kraay standard errors to evaluate differences in monetary policies of Southeast Asian countries over time. The results confirm that expansionary monetary policy has a negative influence on attracting foreign direct investment, while contractionary monetary policy has the effect of promoting the flow of international capital into Southeast Asian countries. The study also confirmed the positive impact of trade liberalization and the quality of human resources on the ability to attract foreign direct investment. However, no effect on foreign direct investment was found for urbanization rate, population size, or number of tourists.
Keywords: 330; monetary policy; FDI; trade